A zágrábi Tudományegyetem hungarológiai tanszékének története - Lőkös, István (Gerundium, 2019)
The author gives an overview on the history of a quarter of a century of the youngest foreign workshop of Hungarian studies, namely, Department of Hungarian Language and Literature of the Faculty of Humanities of the University of Zagreb. The education on Hungarian studies started in Zagreb in 1944 and was precedented. At the University of Zagreb the Hungarian Language Department was functioning as early as the second half of the 19th century. Form 1904 to 1918, for almost one and a half century at the same place Hungarian language and literature was educated with the direction of professor Dr. Kázmér Greska. After the collapse of the Austrian-Hungarian Monarchy the representatives of the Croatian National Council radically put out professor Greska from the university and closed down the department. It was impossible to reorganize it in Yugoslavia between the two world wars. A new possibility came only after the independence of Croatia in 1994. The work in the department restarted on the basis of an interstate contract under the leadership of professor Dr. Milka Jauk-Pinhak and with the partnership of visiting teachers from Hungary. Today, under the management of Orsolya Žagar-Szentesi, 25-30 students start their studies at the department in each year. The function of the special college of translation of poetic works is outstanding. The department in 2002 celebrated the 900 years jubilee of the coronation of Kálmán Könyves as Croatian king with the representative volume of essays entitled Croato-Hungarica. The department was introduced in the „Hungarian issue” of the journal Književna smotra, the Zagreb journal of world literature in 2014 on the 20th jubilee of the department. Their latest publication is With heart and Soul/ Dušom i srcem Hungarian-Croatian Somatic Phraseology/ Mađarsko-hrvatski rječnik somatskih frazema (2018).